2006
DOI: 10.1266/ggs.81.273
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal fluctuation in susceptibility to insecticides within natural populations of Drosophila melanogaster. II. Features of genetic variation in susceptibility to organophosphate insecticides within natural populations of D. melanogaster

Abstract: To elucidate genetic variation in susceptibility to organophosphate insecticides within natural populations of Drosophila melanogaster , we conducted an analysis of variance for mortality data sets of isofemale lines (10-286 lines) used in the previous studies. Susceptibility of isofemale lines to the three organophosphate insecticides was continuously distributed within each natural population, ranging from susceptible to resistant. Analysis of variance showed highly significant variation among isofemale line… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 45 publications
(57 reference statements)
1
12
0
Order By: Relevance
“…In previous studies, not only did we demonstrate that the dynamics of genetic variation in susceptibility to organophosphates within the Katsunuma population can be sufficiently explained by the fluctuation in the frequency of the resistance factor on the third chromosome of the resistant lines, but we also suggested that genetic variation within the Katsunuma population might also be constructed by other factors, such as various Ace alleles as well as the factor on the second chromosome (Miyo and Charlesworth 2004;Miyo et al 2006). Although the numbers of flies newly collected in the field were small, this study demonstrated that genetic variation in susceptibility to organophosphate insecticides within the Katsunuma population is contributed by several genotypes, produced by at least four Ace alleles as well as cytochrome P450 on the second chromosome, therefore confirming the previous suggestion.…”
Section: Discussionsupporting
confidence: 51%
See 3 more Smart Citations
“…In previous studies, not only did we demonstrate that the dynamics of genetic variation in susceptibility to organophosphates within the Katsunuma population can be sufficiently explained by the fluctuation in the frequency of the resistance factor on the third chromosome of the resistant lines, but we also suggested that genetic variation within the Katsunuma population might also be constructed by other factors, such as various Ace alleles as well as the factor on the second chromosome (Miyo and Charlesworth 2004;Miyo et al 2006). Although the numbers of flies newly collected in the field were small, this study demonstrated that genetic variation in susceptibility to organophosphate insecticides within the Katsunuma population is contributed by several genotypes, produced by at least four Ace alleles as well as cytochrome P450 on the second chromosome, therefore confirming the previous suggestion.…”
Section: Discussionsupporting
confidence: 51%
“…This concentration of malathion has been shown to kill a majority of individuals of a standard laboratory strain Canton-S (Miyo et al 2000), and the Katsunuma population has been shown to possess genetic variation in susceptibility to 2.5 lg/cm 2 malathion (Miyo et al 2006). To generate various genotypes regarding the three sites, seven isofemale lines established from the population collected on August 4th were mass-cultured.…”
Section: Contribution Of Point Mutations In the Ace Gene To Survivorshipmentioning
confidence: 99%
See 2 more Smart Citations
“…Although Drosophila flies are not recognized as pest species, insecticide selection pressures have been imposed on the Katsunuma population of Drosophila melanogaster (Meigen), owing to management of other pest species [13]. In fact, the Katsunuma population of D. melanogaster exhibited genetic variation in susceptibility to OPs, which was composed of several resistance factors, including a resistant-type AChE and a cytochrome P450 [14,15]. Therefore, it is conceivable that various agents could mold genetic variation within the Katsunuma population, and that the effects of the fluctuations of genetic variation in OPEN ACCESS susceptibility to one class of insecticides within the population could also affect those to other classes of insecticides simultaneously.…”
Section: Introductionmentioning
confidence: 99%